2016
DOI: 10.1212/nxg.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous deletion in MICU1 presenting with fatigue and lethargy in childhood

Abstract: Objective:To define the mechanism responsible for fatigue, lethargy, and weakness in 2 cousins who had a normal muscle biopsy.Methods:Exome sequencing, long-range PCR, and Sanger sequencing to identify the pathogenic mutation. Functional analysis in the patient fibroblasts included oxygen consumption measurements, extracellular acidification studies, Western blotting, and calcium imaging, followed by overexpression of the wild-type protein.Results:Analysis of the exome sequencing depth revealed a homozygous de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 10 publications
10
95
0
1
Order By: Relevance
“…Nevertheless, pathogenesis in MICU1_KO animals is consistent with that expected from mitochondrial Ca 2+ overload (Liu et al, 2016). The relatively modest matrix free-Ca 2+ elevation under resting conditions may not be the (sole) cause of disease pathogenesis in animal models (Antony et al, 2016; Liu et al, 2016) and patients (Logan et al, 2013; Lewis-Smith et al, 2016; Bhosale et al, 2017). Rather, pathogenesis might be caused by sensitized gain-of-function responses to transient [Ca 2+ ] c signals up to the normal threshold of ~1.3 μM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, pathogenesis in MICU1_KO animals is consistent with that expected from mitochondrial Ca 2+ overload (Liu et al, 2016). The relatively modest matrix free-Ca 2+ elevation under resting conditions may not be the (sole) cause of disease pathogenesis in animal models (Antony et al, 2016; Liu et al, 2016) and patients (Logan et al, 2013; Lewis-Smith et al, 2016; Bhosale et al, 2017). Rather, pathogenesis might be caused by sensitized gain-of-function responses to transient [Ca 2+ ] c signals up to the normal threshold of ~1.3 μM.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of both proteins are controversial in part because over-expression strategies have been used with channel-component stoichiometries not well known, and because MCU-specific Ca 2+ -uptake rates were not rigorously quantitated over a wide range of quantitatively-controlled and recorded [Ca 2+ ] c . The importance of understanding regulation of MCU-channel activity by MICU proteins is underscored by human loss-of-function mutations in MICU1 that result in apparent mitochondrial-Ca 2+ overload and cause early-onset muscle weakness and CNS defects (Logan et al, 2013; Lewis-Smith et al, 2016). Similar pathology and effects on mitochondrial [Ca 2+ ] observed in surviving MICU1_KO mice suggested that constitutive MCU-activity in vivo caused disease pathogenesis (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of MICU1 as a regulatory subunit of MCU is exemplified by the disorders resulting from its misexpression or mutations that alter the EF-hand function (Logan et al, 2014;Xu, 2015;Lewis-Smith et al, 2016;Safari et al, 2016). The bioinformatic analysis reveals highly conserved EF-hand domains in MICU1; this, in turn, might point to an evolutionarily conserved cellular pathway involved in calcium uptake and possibly in calcium signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows a genetic link between mutations in MICU1 and a neuromuscular disease in children. Homozygous deletions in this gene have been additionally implicated with fatigue and lethargy in children (Lewis-Smith et al, 2016), while the single nucleotide polymorphism analysis indicated the role of EF-hand in bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…У фі-бробластах пацієнтів з MICU1-мутаціями акумуляція Са 2+ мітохондріями при низьких [Са 2+ ] с була збільшена [64]. Показано, що делеція гена MICU1 супроводжується ранньою стомлюваністю та млявістю [65]. М´язова дистрофія та центральноядерна міопатія, при яких виявлено порушення Са 2+ -гомеостазу мітохондрій, також можуть бути асоційовані з дефіцитом MICU1 [64].…”
Section: трансмембранний обмін са 2+ в мітохондріях за патологіїunclassified